1988
DOI: 10.3171/jns.1988.68.2.0227
|View full text |Cite
|
Sign up to set email alerts
|

Stereotaxic intracavitary irradiation for cystic craniopharyngiomas

Abstract: Stereotaxic intracavitary irradiation with instillation of phosphorus-32 (32P) colloidal chromic phosphate was performed in nine patients with cystic craniopharyngiomas. Serial neurological, ophthalmological, neuroendocrinological, and radiological examinations were performed before and after treatment. Dosimetry was determined based on a computerized tomography (CT) estimation of tumor volume, and was calculated to provide a tumoricidal dose (200 to 300 Gy) to the cyst wall. The follow-up period ranged from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…Others advocate intracavitary treatments for cystic tumors including irradiation with beta-emitting radioisotopes (phophorus-32 or yttrium-90) 5,33,38,60,61,87,89 or administration of the chemotherapeutic agent bleomycin, an antineoplastic antibiotic that interrupts DNA synthesis. 32,37,54,82 Many reported series utilizing intracavitary therapies are made up of small numbers of patients and usually include small-to moderate-sized, monocystic tumors, not multicystic giant forms.…”
Section: Treatment Options For Giant Craniopharyngiomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Others advocate intracavitary treatments for cystic tumors including irradiation with beta-emitting radioisotopes (phophorus-32 or yttrium-90) 5,33,38,60,61,87,89 or administration of the chemotherapeutic agent bleomycin, an antineoplastic antibiotic that interrupts DNA synthesis. 32,37,54,82 Many reported series utilizing intracavitary therapies are made up of small numbers of patients and usually include small-to moderate-sized, monocystic tumors, not multicystic giant forms.…”
Section: Treatment Options For Giant Craniopharyngiomasmentioning
confidence: 99%
“…32,37,70,82 Intracavitary therapies could prove ineffective for multicystic giant craniopharyngiomas and do not preclude subsequent de novo cyst formation or treat the solid portion of the tumor. 60,61,70 Some authors have demonstrated the ability of intracavitary therapy to decease mass effect via shrinkage or drainage of the cystic portion of the tumor and delay the need for RT in children.…”
Section: Treatment Options For Giant Craniopharyngiomasmentioning
confidence: 99%
“…19 A number of studies have assessed this modality since then. 4,5,7,11,17,21,22,27,28 By and large, these studies have shown good cyst control with 1 or more instillations of P32 or yttrium-90. Almost all of these studies (including one from our institution) included patients who underwent multiple modalities of therapy, including varying degrees of resection and EBR.…”
Section: Discussionmentioning
confidence: 85%
“…Patients in this study did undergo EBR therapy prior to or concomitant with intracystic therapy. Pollack et al 21 published an early experience with P32 instillation in 9 patients. Their study showed significant reduction in cyst size on follow-up imaging in all patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation